Islamic Communication in Mandailing Culture: Unveiling Elements of Da'wah within Markobar Tradition - Farid, Ahmad Salman; Muhammad Ardiansyah (Jurnal Komunikasi Islam, 2024)
This study examines the relationship between markobar and Islamic communication, particularly to unveil the elements of Islamic proselytizing (da’wah) within markobar tradition. The method employed in this study was a qualitative approach. Data was collected through literature review, observations, and interviews with key informants. The observation was conducted at funeral ceremonies and traditional Mandailing weddings. The collected data from the field and documents was analyzed using a thematic analysis approach. The findings illustrate that there are Islamic communication styles embedded within markobar tradition, namely qaulan sadida, qaulan baligha, qulan ma'rufa, qaulan karima, qaulan layyinan, and qaulan maysura. Additionally, this Mandailing culture is also considered to represent a means of da’wah and to contain da’wah messages to promote goodness and discourage bad deeds (amar ma'ruf nahi munkar).